2020
DOI: 10.1093/mnras/staa2424
|View full text |Cite
|
Sign up to set email alerts
|

Seeing above the clouds with high-resolution spectroscopy

Abstract: In the last decade, ground-based high-resolution Doppler spectroscopy (HRS) has detected numerous species in transiting and non-transiting hot Jupiters, and is ideally placed for atmospheric characterization of warm Neptunes and super Earths. Many of these cooler and smaller exoplanets have shown cloudy atmospheres from low-resolution near-infrared observations, making constraints on chemical species difficult. We investigate how HRS can improve on these given its sensitivity to spectral line cores which probe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 98 publications
6
35
0
Order By: Relevance
“…Our results statistically favour the presence of aerosols in the atmosphere of HD 209458b (Extended Data Fig. 4), which dampen the amplitude of the molecular lines but do not evidently hamper their detection 24,25 . This supports the results of other observations of this planet (see Methods).…”
supporting
confidence: 65%
“…Our results statistically favour the presence of aerosols in the atmosphere of HD 209458b (Extended Data Fig. 4), which dampen the amplitude of the molecular lines but do not evidently hamper their detection 24,25 . This supports the results of other observations of this planet (see Methods).…”
supporting
confidence: 65%
“…Following the receipt proposed by [9], we thus converted the cross-correlation values into likelihood values, and we used the likelihood-ratio test to compare the different models. Our results statistically favour the presence of aerosols in the atmosphere of HD 209458 b which dampen the amplitude of the molecular lines but do not evidently hamper their detection [23,26]. Furthermore, the atmospheric models we tested in thermochemical equilibrium seem to prefer a carbon-to-oxygen ratio close to or greater than 1, higher than the solar value (0.55).…”
Section: Observations and Analysis Of Giano-b High-resolution Spectrasupporting
confidence: 60%
“…Finally, complementary information on K2-18b's atmosphere could be provided by high-resolution Doppler spectroscopy from ground-based instruments. Such observations can be efficient to probe cloudy atmospheres and to constrain abundances and cloud-top pressure (Gandhi et al 2020). As shown by Blain et al (2021), one full transit of K2-18b observed with VLT-CRIRES+ might be sufficient to detect CH 4 .…”
Section: Observational Transit Spectramentioning
confidence: 95%